Cross-blockchain architecture for secure storage and verification of vaccination records - Lim, Jasper Bing Hong (Nanyang Technological University, 2022)
Following the ongoing battle against COVID-19, countries have been shifting from a lockdown focused strategy towards a vaccination strategy to combat rising infection rates. Countries that have previously closed their borders to prevent import infections have also begun to open to gain the social and economic benefits that come with open borders. To prevent setting back progress with the fight against the virus, multiple countries thus require proof of vaccination before entry. However, there is currently no agreed upon method for vaccination record sharing and validation system between countries. This paper proposes an architecture leveraging on blockchain technology to allow different countries to store vaccination records in their own blockchain networks and be able to universally verify vaccine information between these networks without sharing of raw data.